Canine Hepatopathology: Clinical Manifestations, Pathophysiology and Diagnostic Considerations - A Review - Jyothi, K.B.,; M.G.Jayathangaraj,; G.Poojitha,; S.Umamageswari, (The Indian Veterinary Journal, 2026)
Hepatic diseases in dogs represent a complex group of disorders with diverse etiologies and manifestations. This paper reviews the current understanding of canine hepatopathology, including clinical symptomatology, underlying pathophysiological mechanisms and diagnostic considerations. The liver's remarkable regenerative capacity and its central role in metabolism make hepatic disorders particularly challenging to diagnose and manage in veterinary practice. Various clinical manifestations of hepatic diseases/disorders have also been dealt with in this paper. This review aimed to provide veterinary practitioners with an integrated understanding of canine liver diseases, from cellular injury mechanisms to clinical presentation patterns.